Kinetic strategies of gymnastics landings - Straker, R.; Exell, T.; Farana, R.; Hamill, J.; Irwin, G. (ISBS Proceedings Archive (Michigan), 2022)
Organisation and magnitude of lower limb kinetics during landing can contribute to knowledge of injury. Our aim was to quantify leg stiffness and temporal organisation of joint moments of two different landing styles. Four female gymnasts performed 20 landings in the women`s and men`s landing style. Synchronised kinematic (250 Hz) and kinetic (1000 Hz) data were used to describe the leg and joint stiffness, and the sequencing of the peak joint moments. Leg stiffness demonstrated lower variability compared to the associated joint level, suggesting joint level control. Group relative timing of the lower extremity joint moments presented distal-proximal sequencing, although individuals presented a variety of landing strategies. This study highlights the individualised signature strategies in landing, and consequently the importance of a single-subject design when examining injury risk.